Beyond instrumentalism: Broadening the understanding of social innovation in socio-technical energy systems - Wittmayer, Julia M. (2020)
Social innovation is an important dimension of current transformations in energy systems. It can refer to alternative business models, novel policy instruments, financing schemes, participatory governance approaches to energy questions, or new discourses. Its significance for energy systems is often considered in narrow instrumentalist terms, reducing it to a tool serving particular policy objectives. Grounding the concept in social science and humanities insights, this review essay proposes a broadened social innovation understanding. We propose 1) to open up the normative complexity of the concept; 2) to appreciate the multi-actor nature of social innovation; 3) to understand it as an analytical entry point for socio-material intertwinement; and, 4) to understand social innovation as premised on experimentalism-based intervention logics. The proposed social innovation understandings provide a broader imagination and strategizing of structural changes in energy systems.